The Social Class Worldviews of Chinese International Students in the United States - Garrison, Yunkyoung; Park, Soeun; Yeung, Chi W.; Li, Zongqi; Ho, Yu Chak Sunny; Chang-Tran, Jennifer (Journal of International Students, 2022)
In this qualitative study, we investigated the social class worldviews of Chinese International Students (CIS) in the United States. Social class worldviews are a constellation of beliefs, attitudes, and values that individuals use to maintain a sense of psychological equilibrium within their perceived social class groups and culture. Having interviewed eleven CIS in a midwestern city in the United States, the researchers found that their experiences reflected five themes: (a) social class consciousness; (b) social class socialization; (c) social class resources; (d) social class values; and (e) social class challenges. Suggestions for research and implications for higher education are discussed.